KARAKTERISTIK AKSEPTOR KB PIL DI PUSKESMAS KESAMBI KECAMATAN MARGASARI KABUPATEN TEGAL - Wilis Sukmaningtyas; Devi Ratna Puspitasari (Universitas Harapan Bangsa Purwokerto, 2011)
Population problems in Indonesia is a large population growth with the population growth rate is relatively high. One of the government's efforts to suppress the population growth that is by imposingprogrm KB. The use of birth control pills in Central Java, 23.3% sabagai reason a woman uses birthcontrol pills are very effective because, age and parity is one factor driving the use of contraceptives. InTegal regency, approximately 12.79% were using contraceptives birth control pills and preliminarysurveys have been conducted in sub-district Puskesmas Kesambi Margasari Tegal 553 pill acceptorsacceptors. This study aimed to describe the characteristics of family planning acceptors of pills at healthcenters Margasari Kesambi District of Tegal in 2011. This research method is quantitative descriptive study using a retrospective approach. Thepopulation of this study were 113 respondents who use contraception pills in January-December 2009and the sampling technique using total sampling. The type of data using secondary data is done manuallyby recording the data from the register book and included in the master table. Characteristics of 113 acceptors of family planning acceptors pills are mostly aged 20-35 years67 respondents (57.5%), a small portion of acceptors over the age of 35 years and 6 respondents (5.3%),mostly primiparous 79 respondents (69, 9%), a small portion multiparas 34 respondents (30.0%). The characteristic feature of family planning acceptors of pills at health centers MargasariKesambi District of Tegal in 2009 the dominant aged 20-35 years and primiparous parity. Keywords: Characteristics, Acceptors KB, contraceptive pills.